NUMERICAL STUDY OF THE BUBBLE FORMATION MECHANISM IN HORIZONTAL LIQUID-GAS FLOW IN A T-JUNCTION MINICHANNEL - Widodo, Gilang Destya; Dharma, Untung Surya; Deendarlianto, Deendarlianto (Jurnal Rekayasa Mesin, 2025)
The purpose of this research was to study the mechanism of air bubble formation at the T-Junction Minichannel. Numerical simulations were carried out using the Volume of Fluid (VOF) method on OpenFOAM v2112 with the Pressure Implicit with Splitting of Operators (PISO). Working fluids of water and air were simulated in a T-junction minichannel with a rectangular cross section size of 1.25 x 2.25 mm with a hydraulic diameter of 1.6 mm and a connection radius of 1.12 mm. Two-phase flow is simulated using samples in the air speed range Ug = 0.59 m/s – 1119 m/s and water speed Ul = 0.81 m/s – 1.16 m/s. The results showed that the mechanism for the formation of air bubbles is influenced by the water flow mechanism which maintains the volumetric flow rate along with the growth of air bubbles in the flow cross-section direction which causes an increase in water velocity in the gap between the flow interface and the wall, so the shear stress of the water flow increasing at the flow interface causes the air bubbles to be pushed to flow faster. The velocity of water and air flow increases as the flow cross-sectional area of each phase decreases and a rotational flow occurs in the air bubble area when the air bubble initially forms. Pressure increase occurs in the flow of air and water just before the air bubble break up and a pressure decrease significantly when the air bubble break-up.